Beasts we love - Masolane, Tseliso Chrisjan (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2018)
My thesis is a novella in flash, written as political crime fiction. It is set in contemporary South Africa and tells the story of Rafau Lekopo, a teacher from a little township called Dikgohlong, whose life is changed forever after he finds his wife and the mayor in bed and shoots them both dead. The information contained within the dead mayor's notebook proves to be explosive, showing that the mayor is far more than he seems, and that he is in fact in the employ of a foreign intelligence service. After his release from prison, the embittered Lekopo sets about his revenge against powerful men who abuse their political power. He takes refuge in Lesotho, masterminds a series of heists, car-hijackings and human trafficking, and expands his syndication back in South Africa. Using the contacts and information from the mayor's notebook, he manipulates the Lesotho government into a diplomatic feud with South Africa which treatens to escalate into a military conflict.
Keywords: Creative writing (Higher education) -- South Africa; South African fiction (English) -- 21st century; Detective and mystery stories, South African (English) -- 21st century